Current understanding of the mesenchymal stem cell-derived exosomes in cancer and aging - Muralikumar, Makalakshmi (Biotechnol Rep (Amst), 2021)
Mesenchymal stem cells (MSCs) are being widely researched upon for several years with translational application in regenerative medicine. Many studies acknowledged trophic factors from MSCs, attenuating dreadful ailments. The beneficial properties of MSCs are attributed to their secretion of paracrine factors as extracellular vesicles/ exosomes in the tissue microenvironment. Exosomes are nano-sized vesicles involved in genetic material transportation and intercellular communication. Exosomes have been recently reported to play a role in cell-free therapy in treating many diseases like cancer and aging and are reported in regulating tumor cell fate. This review highlights the recent advances and current understanding in assessing mesenchymal stem cell-derived exosomes for possible cell-free therapy. The sources and composition of exosomes, drug delivery effectiveness, immunomodulatory property, therapeutic advances in cancer, and aging targeting exosomes as cargo or its effect to moderate the tissue microenvironment are also discussed. We summarize the regenerative mechanisms induced by MSCs derived exosomes.